Optimizing Analysis Of The Radiographic Image And Entrance Surface Dose Using Computed Radiography In Chest Examination - Nursama Heru Apriantoro; Budi Santoso; Purwantiningsih Purwantiningsih; Tri Ambarsari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
This research has conducted about exposure factor variation analysis examination of the thorax surface dose and image noise in radiography. Do 10 (ten) times the exposure in the thorax phantom with various exposure factor such as 50 kV- 8 mAs, 50 kV-10 mAs, 55 kV- 8 mAs, 55 kV-10 mAs, 55 kV-10 mAs, 60 kV- 8 mAs, 60 kV-10 mAs, 66 kV-8 mAs, 66 kV-10 mAs, and 102 kV- 1 mAs, 102 kV - 2,5 mAs for high kV technique. For each exposure factor the pinned , TLD placed in the middle of the field to measure the radiation dose level. The optimum exposure conditions of the thorax PA examination (expressed with IgM value) occurs when using exposure factor 55 kV and 8 mAs for IgM values ​​obtained are 1.91, 6.605 for standard deviation values ​​and ESD 0.098 mGy.